Pengembangan Aplikasi Traveling Social Media Dengan Scrums - Tri Septianto (Jurnal Teknika, 2020)
As an application developer usually needs to do project management to work on a project. Project management is a strategy used to complete a project. Project management methods vary greatly. One of them is the scrums method. This method prioritizes individual tasks, then delegates those tasks to the team members who are considered the most appropriate for completing those tasks. The application of the Scrums method is iterative or repeated using a different backlog. In this study the Scrums method is applied in the development of social media application projects such as Instagram but is more specific in traveling activities. The development of this project was given a time of work for seven weeks. So in this study we documented all the processes in the Scrums method that we carried out in order to be a reference in making application strategies.